Activation and conformational dynamics of a class B G-protein-coupled glucagon receptor. Issue 18 (20th April 2016) - Li, Yang; Sun, Jixue; Li, Dongmei; Lin, Jianping
Abstract : The binding of the agonist glucagon would induce the conformational dynamics and activation of the GCGR. The activation led to the outward movement of helix VII and breaking of two hydrogen bonds. Abstract : The human glucagon receptor (GCGR) is a class B G-protein-coupled receptor (GPCR). The GCGR can be activated by glucagon and regulates the release of glucose. The GCGR has been proposed to be an important drug target for type 2 diabetes. Based on the structural model of a full-length glucagon-bound GCGR (glu-GCGR), we performed accelerated molecular dynamics (aMD) simulations, potential of mean force (PMF) calculations, cross-correlation analysis and community network analysis to study the activation mechanism and the conformational dynamics during the activation process. The PMF map depicts three different conformational states of the GCGR: the inactive, intermediate and active states. The activation of the GCGR is characterized by the outward movement of the intracellular side of helix VI. In the active state of the GCGR, the Arg173 2.46 –Ser350 6.41 and Glu245 3.50 –Thr351 6.42 hydrogen bonds break, and the χ 1 rotamer of Phe322 5.54 changes from perpendicular to parallel to helix VI. The binding of the agonist glucagon decreases the correlated motions of the extracellular loops (ELCs) and the helices around the glucagon-binding site. During the activation of the GCGR, the connections between the intracellular sides of helices become weaker, and the connections between glucagon and ECLs and the extracellular sides of helices become stronger. These facilitate G-protein coupling on the intracellular side and glucagon binding on the extracellular side, and stabilize the GCGR in the active state. We expect that this study can provide useful information on the activation mechanism of the GCGR and facilitate the future design of GCGR inhibitors.